Design of Microstrip Antenna Array for 5G Communication Systems - Mimsyad, Muhammad; Rauf, Awaluddin; Rauf, Yuliana (Jurnal Teknologi Elekterika, 2025)
For the time being, the fifth generation (5G) communication system has been realized in many countries and the number of 5G subscribers is very large. Unlike previous generations that only focused on improving network capacity, the 5G communication systems extends telecommunication services from humans to objects (things), and also from consumers to industries. This enables a wide range of services from conventional mobile broadband to industry 4.0, virtual reality (VR), Internet of Things (IoT), and automatic driving. The values ​​of 5G services and applications greatly support the mobility and flexibility of today's customers such as remote surgery in hospitals, online education, driverless vehicles, unmanned delivery, robots, smart healthcare, industrial automation. This study presents the design and realization of a 4×4 rectangular microstrip antenna array. This antenna can be applied to support 5G communication. The antenna array configuration is arranged uniformly. For antenna excitation, an inset feed transmission line is employed to each antenna element. The antenna array has been validated and works at a frequency of 2.3 GHz, with an HPBW of 30° in the E-plane. Meanwhile, based on measurements, the gain and bandwidth values ​​are 13.51 dBi and 100 MHz respectively.